MGIMO-UNIVERSITY MASTER’S DEGREE IN REGIONAL STUDIES ”POLITICS AND ECONOMICS OF WORLD REGIONS” (Сравнительная политика)
MGIMO-University Master’s Degree in Regional Studies ”Politics and Economics of World Regions”.